Transformation of the Yakut Heroic Epos Olonkho: Statement of the Problem, Systematization and Periodization - A. A. Kuzmina (Научный диалог, 2019)
The article is devoted to the transformation of the Yakut heroic epos. The relevance of the work is due to large changes in the epos creation of Yakut storytellers and insufficient study of this process in Yakut folklore. The novelty of the study is that for the first time the problem of olonkho transformation is specifically studied. Various changes in the epos in the genre, pragmatic, conceptual, ideological and other aspects are considered. Of particular note is the transition from the oral epos to the written form of being. It is established that the appearance of copyright works based on olonkho creates confusion in the definition of the genre, as a result of which various falsifications appear. The characteristic of the transformation of the concept of “olonkhosut” (narrator) is given. An author’s periodization of olonkho transformations is proposed, which consists of three stages: pre-revolutionary, Soviet and post-Soviet (modern). It is noted that each period has its own characteristics. The author of the article reveals some features of stage productions when traditional images and motives of olonkho are distorted to suit modern viewers' requirements. Summing it up, the author concludes that the transformation of the epos creates a great danger that can destroy the olonkho genre in Yakut folklore and change the idea of it in modern people.